Sequence of image enhancemant of flat electroencephalography using intuitionistic fuzzy set - Suzelawati Zenian, 1980- , author; Tahir Ahmad, 1963- , supervisor; Amidora Idris, 1978- , supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Ph.D (Matematik)) - Universiti Teknologi Malaysia, 2018